Practical application of non-contact alternating current electric field mixing for reagent-saving in situ hybridisation of HER2. Issue 9 (25th May 2019) - Kurihara, Nobuyasu; Imai, Kazuhiro; Nanjo, Hiroshi; Nakamura, Ryuta; Wakamatsu, Yuki; Akagami, Koji; Terata, Kaori; Wakita, Akiyuki; Sato, Yusuke; Motoyama, Satoru; Akagami, Yoichi; Minamiya, Yoshihiro
Abstract : Aims: Human epidermal growth factor receptor 2 (HER2)-targeted agents are effective against HER2-positive breast cancers. However, their lack of survival benefit in HER2-negative patients as well as their toxic effects and high cost highlight the need for accurate assessment of HER2 status. Our aim was to evaluate the clinical utility of a reagent-saving in situ hybridisation (Saving ISH) that facilitates hybridisation and saves HER2/chromosome enumeration probe by taking advantage of the non-contact mixing effect of an alternating current (AC) electric field. Methods: With a new device, we apply a high-voltage, low-frequency AC electric field to the tissue sections, which mixes the probe within microdroplets as the voltage is switched on and off. Specimens (n=113) from patients with breast cancers identified immunohistochemically as HER2 0/1(+), (2+) or (3+) were used. The specimens were all tested using conventional dual ISH (DISH), DISH with an automated slide stainer (ASS) and Saving ISH (1:1–1:3 dilution). Results: The Saving ISH with 1:2 probe dilution produced stable results with less non-specific staining while using smaller amounts of probe. The accuracy of HER2 status with Saving ISH was equal to standard. We found 96.4% agreement between DISH using ASS and Saving ISH (kappa coefficient=0.912). Conclusions: These results suggest reagent-saving HER2 ISH could be used as a clinical tool for accurate and stable HER2 assessment, even when reagent concentrations vary.